THE USE OF RADAR TECHNOLOGIES IN THE HYDRAULIC ENGINEERING IN SEISMIC ZONES: The use of radar technologies in the hydraulic engineering in seismic zones - Oralbekova, Zhanar O.; Tyulepberdinova, Gulnur A.; Gaziz, Gulnur G.; Adamova, Aigul D.; Sholpanbaev, Bakytgerey B. (Journal of Applied Engineering Science, 2021)
Hydraulic structures are designed in a standard way if it is necessary to regulate the water course and maintain the volume of irrigation. The obstacles to the construction of such structures are mainly technical and economic, when instead of building a new hydraulic complex, it is gradually modernised. Consideration of the issues of creating complexes of hydraulic structures leads to the statement of a fact that the water balance of the territory changes. The novelty of the study is determined by the fact that hydraulic structures can be used as prerequisites for the development of qualitatively new programmes for runoff regulation. The authors note that this is particularly important for seismologically unstable areas. It is necessary to lay out plans taking into account not only the possible seismological load, but also the modes and technologies that are used to modernise the already operating hydraulic structures. The practical significance of the study is determined by the fact that the development of hydrotechnical complexes makes it possible to create a system not only for improving the quality of the water balance, but also performs technological support for the safety of the technologies used.